Impacts of Urban Traffic Jams on Physical Health of Residents from the Inhabitants 'Perspective in Sanandaj City(A Qualitative Study) - Haidar Nadrian; Mohammad Hossein Taghdisi; Mehran Aghemiri; Maryam Khazaee-Pool; Davoud Shojaeizadeh (Iranian Association of Health Education and Health Promotion, 2017)
Background and Objective: Traffic jams and transportation are an important part of the spectrum socioeconomic and environmental factors outside the health system with impacts on health. The aim of this study was to explain the residents' viewpoints about the impacts of urban traffic on their physical health in Sanandaj. Materials and methods: The study was carried out qualitatively with content analysis method in 2014. Twenty-two residents of the city were selected as participants who were interviewed in a Focus Group Discussions (FGDs) (4 sessions) and in-depth individual interviews (8 sessions), respectively. A purpose-based sampling method was used in this study. The MAXQDA10 software was applied to facilitate the coding and categorizing the data. Results: Based on the viewpoints of the participants, urban traffic jams has two direct and indirect negative impacts on physical health. The direct effects cause premature aging, excessive fatigue, and mental illness and make some problems in the musculoskeletal system, digestive system, nervous system, respiratory system, cardiovascular system. The indirect influences include pure reliance on the car, accidents, traffic congestion and air pollution.   Conclusion: Healthcare researchers and urban traffic policymakers should design comprehensive studies to assess the impacts of urban traffic jams and transportation on community health. Therefore, they would be able to investigate the impacts on the health of individuals after the enactment of each law and planning and to implement community-based health promoting strategies in the society.